KELENGKAPAN PENGISIAN INFORMED CONSENT RAWAT INAP PADA PASIEN BEDAH UMUM GUNA MENUNJANG ASPEK HUKUM DI RSUP DR. HASAN SADIKIN BANDUNG - Wowo Trianto (UPPM Politeknik TEDC Bandung, 2018)
Based on a preliminary study that was conducted in RSUP Dr. Hasan Sadikin Bandung in 2018 stated that accomplishment of the average completeness was 92.03% and 7.97% achieved the incompleteness, this will have an impact on the law aspects of health services in RSUP Dr. Hasan Sadikin Bandung. The research method used quantitative research, Techniques of data accumulation was done by observation, interview and review of the literature. Results of the study showed the completeness average of filling in January and February 2018 was 206 or (91.26%) with the highest incompleteness in the variable No medical record and provide action to is (67.26%) as well as filling the relationship with the patient registration (61.95%), on filling the recipient information registration (60.18%) and on filling the gender registration (57.08%) with an average of as much as 142 files or of 62.74%. As for the advices given by the author as follows: (1) we recommend that doctors and nurses follow existing procedures in order to law aspects can be according to SPM (Permenkes RI No. 129/Menkes/SK/II/2008 about the minimum service Standards (SPM) Hospital), (2) We recommend that form Informed Consent must be done hand in hand with the handling of patients in order to reduce the number of incomplete form Informed Consent, (3) we recommend that there is the cooperation between the medical record officers and the doctors or nurses to communicate or coordinate with each others in term of form Informed Consent filling.